Tight Competition of Local And Foreign Migration in Riau Island: Does Increase Population Inequality Level? - Fitrisia Munir (Journal of Diplomacy and International Studies, 2018)
ASEAN is a group of countries that collaborate and have strategic strength in the Southeast Asia region to overcome various development problems, especially population problems. The ASEAN region as an integration of countries adjacent to developed countries began to experience anxiety in dealing with the problem of development inequality, especially the competition of local and foreign populations which increased in one region. Some researchers explain that a measure of inequality in the world can be seen from the low regional income of developing countries compared to developed countries. (Houghton, 2010) reveals that population inequality is also caused by geographical and cultural factors that do not support the development process which results in wider population differences than poverty. However, population inequality is a development problem caused by overcrowding of immigrants in areas that cannot be controlled. The emergence of high competition of local and foreign populations has resulted in an unbalanced area. This article aims to evaluate population inequalities from the perspective of high competitiveness by local and foreign residents who come from outside which suppress the existence of indigenous people to work. In addition, the impact of population competition can result in widespread marginalization of indigenous people.